Integration of Sapta Jiwa Value in Prophetic Leadership to Improve Santri Character Education in Islamic Boarding Schools - Pamungkas, Sahril Dwi; Ichwanudin (Jurnal Pendidikan Nusantara, 2025)
The character crisis that occurs in young people is the main problem in national education. Various literature describes how the concept of character education in national education failed. This research aims to explain the idea of prophetic Leadership based on examples in the educational environment as an offer of solutions to these problems. Using a qualitative descriptive approach, this research is expected to reveal prophetic leadership practices located at the Daruttaqwa Islamic Boarding School, which has been dedicated for 14 years to shaping the character of teenagers. The results of the study revealed that the integration of Sapta Jiwa Pondok Pesantren Daruttaqwa with the concept of prophetic Leadership reflects values such as Sadiq (honesty) in simplicity and sincerity, Trust in obedience and responsibility, and tabligh in the totality of ukhuwah and sacrifice. Fathanah (intelligence) is manifested in intellectual, emotional, and spiritual intelligence. The concept of boarding school in this Islamic boarding school provides a social interaction experience that hones the emotional intelligence of students. The incorporation of these values in the curriculum and the lives of students shows the dedication of leaders and educators in building a comprehensive character education.